2013
DOI: 10.1097/psy.0b013e318286f949
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Letters From Fall and Bailey, and Muldoon

Abstract: Two letters were recently submitted to the editor regarding our recent publication (1), both of which raised important issues. Fall and Bailey identified discrepancies between their work (2) and ours, which deserve consideration. They also used the same Dill and Costill correction technique (3) after maximal exercise, though it yielded different results to their study and one by Darlington and colleagues (4). Darlington and colleagues found that progressive dilutions from 0-90% of citrated plasma elongated coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…52 Acute stressinduced changes in plasma volume only explain between 4 and 10% of the variance in changes of FVII:C, FVIII:C, and FXII: C. 49 The most accurate methods to investigate the relative contribution of stress-hemoconcentration to the acute prothrombotic stress response are of current debate. [53][54][55] Arithmetic adjustment for stress-hemoconcentration has differing effects on fibrinogen, FVII:C, FVIII:C, FXII:C, VWF:Ag, PT%, and aPTT. 31,56 Saline reconstitution of contracted plasma suggested that stress-induced elevations of most measures was due to hemoconcentration, with the notable exception of FVIII:C. 31 In fact, no correction technique removed the effects for FVIII:C, suggesting that the intrinsic pathway is genuinely activated during acute stress.…”
Section: Underlying Physiological Mechanisms With Acute Stressmentioning
confidence: 99%
“…52 Acute stressinduced changes in plasma volume only explain between 4 and 10% of the variance in changes of FVII:C, FVIII:C, and FXII: C. 49 The most accurate methods to investigate the relative contribution of stress-hemoconcentration to the acute prothrombotic stress response are of current debate. [53][54][55] Arithmetic adjustment for stress-hemoconcentration has differing effects on fibrinogen, FVII:C, FVIII:C, FXII:C, VWF:Ag, PT%, and aPTT. 31,56 Saline reconstitution of contracted plasma suggested that stress-induced elevations of most measures was due to hemoconcentration, with the notable exception of FVIII:C. 31 In fact, no correction technique removed the effects for FVIII:C, suggesting that the intrinsic pathway is genuinely activated during acute stress.…”
Section: Underlying Physiological Mechanisms With Acute Stressmentioning
confidence: 99%